How Workaholic Leadership Affects Employee Self-Presentation: The Role of Workplace Anxiety and Segmentation Supplies - Zeng, Qi; Liu, Xin (Frontiers in Psychology, 2022)
In an increasingly competitive and performance-oriented society, workaholic leadership is becoming increasingly common and is even embraced and supported by many organizations. However, previous studies have not paid sufficient attention to the impact of workaholic leadership on employee psychology and behavior. This study, based on the conservation of resources theory, explores the effect of workaholic leadership on employee self-presentation. Through an empirical analysis of 256 employees' questionnaires, we found a significant positive impact between workaholic leaders and employee self-presentation. This process was achieved through the partly mediating mechanisms of employee workplace anxiety. Concurrently, segmentation supplies negatively moderated the relationship between workplace anxiety and self-presentation and the overall mediating mechanism. These findings provide important insights into the underlying mechanisms of workaholic leadership and employee behavior, which can be utilized to improve employee wellbeing and provide positive organizational outcomes.